Chatbots and crisis communication: effectiveness and limitations in the educational sector - BaaJ , Kaoutar; El Bakkali, EL Arbi; Amine Lahiala, Mohamed (Cadernos de Educação Tecnologia e Sociedade, 2024)
Chatbots play an increasingly significant role in crisis communication by providing real-time information and reducing misinformation. This article explores their application in the educational sector, focusing on their effectiveness during crises. The COVID-19 crisis underscored the urgency of robust communication solutions to ensure accurate and timely sharing of information. The educational sector, serving large and diverse populations, faces unique challenges during emergencies. These challenges include the need to quickly and reliably convey information to a wide range of individuals, including students, parents, teachers, and administrative staff. By integrating chatbots, these institutions can enhance user satisfaction by providing immediate and relevant responses while maintaining educational continuity despite disruptions. However, technological and social limitations persist. Challenges such as the accuracy of AI-provided responses, the linguistic and cultural adaptability of chatbots, and user trust need to be addressed. This research proposes solutions to overcome these obstacles by examining various use cases and drawing on empirical study. The findings demonstrate that, while chatbots cannot fully replace human communicators, they are valuable tools for enhancing communication strategies and supporting educational communities during crises. Their ability to deliver real-time updates, reduce misinformation, and offer emotional support makes them indispensable for crisis communication in the educational sector. With proper implementation and continuous improvement, chatbots can play a pivotal role in crisis management, ensuring that educational processes remain uninterrupted and stakeholders receive reliable information and continuous support. This study emphasizes the need for ongoing innovation and research to optimize chatbot technology for crisis communication, making the educational sector more resilient and adaptable to emergency situations.